Helicopters - Stille, Darlene R. (Minneapolis, MN : Compass Point Books, 2004)
A simple introduction to different kinds of helicopters and their uses.
Includes bibliographical references (p. 30) and index.
4.5
K-3
Keywords: Helicopters -- Juvenile literature; Helicopters; Helicopters